2009
DOI: 10.2478/v10141-009-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Elite Young Team Players' Coping, Motivation and Perceived Climate Measures

Abstract: IntroductionSport psychology researchers have been investigating different means and forms of exercises to better support coaches and scouts in recruitment, talent development (Sands and McNeal 2000), and also to enhance athletic performance . Most investigations are based on the assumption that psychological characteristics should be considered as important determinants of athletic performance and success (Smith and Christensen 1995). Recently researchers have made an effort to reveal the most relevant psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…In terms of the coach motivational climate and players’ gender, the results were in line with previous studies showing that boys perceive higher coach ego climate than girls, who perceive a more task-involving climate [18,55,65,66,67,68,69,70,71]. These results, which only refer to the coach climate, show that boys still tend to interpret sports as a competitive context while girls have better internalized the cooperative and leisure aspect of sports.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the coach motivational climate and players’ gender, the results were in line with previous studies showing that boys perceive higher coach ego climate than girls, who perceive a more task-involving climate [18,55,65,66,67,68,69,70,71]. These results, which only refer to the coach climate, show that boys still tend to interpret sports as a competitive context while girls have better internalized the cooperative and leisure aspect of sports.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the results were in line with other studies where women's perception of a mastery climate was higher than men's and the performance climate is higher in men. 44,47,54,73,7779 In contrast, in the study conducted by Møllerløkken et al. 48 with similarly aged football players, the results reflected that both genders perceived that the motivational climate was significantly more performance-oriented and much less master-oriented.…”
Section: Discussionmentioning
confidence: 75%
“…As for the gender of the athletes and the different variables analysed in this study, the literature on the relationship between the motivational climate generated by the coach and the gender of the players, the results reflect statistically significant differences in which the perceived performance climate is greater in boys and the mastery climate is greater in girls. 4,4447 However, there are also other studies that do not reveal significant differences and where only differences were obtained in terms of competition climate, with a higher result for boys. 48 In relation to the implicit beliefs about sports ability and this sociodemographic variable, few studies have been found, with contradictory conclusions 4951 and even in some of the cases no statistically significant differences were found.…”
Section: Introductionmentioning
confidence: 90%
“…Berdasarkan hasil penelitian sebelumnya dapat dilihat bahwa atlet wanita memiliki tingkat kebosanan yang lebih tinggi bila dibandingkan dengan atlet pria di berbagai olahraga (Cremades & Matius, 2008). Selain itu, atlet wanita memiliki kemampuan untuk mengatasi kesulitan, tekanan, penetapan tujuan, Motivasi intrinsik dan persiapan mental yang lebih rendah bila dibandingkan dengan atlet pria (Gábor, et al, 2009 Partisipasi dalam olahraga cenderung diidentifikasi dengan karakteristik pria seperti kecepatan dan kekuatan, menyebabkan masalah gambar bagi atlet wanita (Knight & Giuliano, 2003…”
Section: Pembahasanunclassified